Factors Affecting Exclusive Breastfeeding in The Work Area - Mursalini Mursalini; Mappeaty Nyorong; Endang Maryanti (Jurnal Perilaku Kesehatan Terpadu, 2022)
The future quality of Human Resources (HR) can be improved by the provision of optimally nutritious breast milk (ASI), which boosts the child's immunity and cognitive abilities. Both mom and baby benefit greatly from a period of exclusive breastfeeding throughout the first six months. Women who breastfeed their infants exclusively are still in the minority (80%). There are a total of 673 infants registered at the Pekan Labuhan Health Centre, but only 57 of them are receiving exclusive breastfeeding, which is only a small fraction of the national goal. Predisposing factors, enabling factors, and reinforcing factors all contribute to whether or not a mother chooses to breastfeed exclusively. To determine what factors, affect exclusive breastfeeding in the 315-person catchment area of the Pekan Labuhan Health Centre, this study employs a cross-sectional, analytical survey approach. With the use of the Slovin formula, we were able to collect data from 76 individuals. Using a questionnaire to gather information. Multiple methods of data analysis, including univariate and multivariate were used. All significantly influenced her likelihood of breastfeeding exclusively. There was no difference made by education, upbringing, or social networks. With an Exp(B) value of 28,794, mother's employment status is the most significant influencer of whether or not a mother gives exclusive breastfeeding compared to mothers who do work. health workers' access to training, employment, positive attitudes, and social support. It is suggested that the District Government implement more frequent counselling and organize a support group for moms to help them maintain exclusive breastfeeding.